Resource sharing in biomedical research - Berns, Kenneth I., 1938-; Bond, Enriqueta C.; Manning, Frederick J. (National Academy Press, 1996)
The United States is entering an era when, more than ever, the sharing of resources and information might be critical to scientific progress. Every dollar saved by avoiding duplication of efforts and by producing economies of scale will become increasingly important as federal funding enters an era of fiscal restraint. This book focuses on six diverse case studies that share materials or equipment with the scientific community at large: the American Type Culture Collection, the multinational coordinated Arabidopsis thaliana Genome Research Project, the Jackson Laboratory, the Washington Regional Primate Research Center, the Macromolecular Crystallography Resource at the Cornell High-Energy Synchrotron Source, and the Human Genome Center at Lawrence Livermore National Laboratory. The book also identifies common strengths and problems faced in the six cases, and presents a series of recommendations aimed at facilitating resource sharing in biomedical research.